2020
DOI: 10.1021/acs.cgd.9b01182
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Crystal Distribution Uniformity Based on the CVD Method with the Aid of Finite Element Methods

Abstract: Two-dimensional materials, including transition-metal dichalcogenides (TMDs), have aroused wide interest due to their various applications in gas sensors and photoelectric devices. However, achieving a uniform distribution of materials on the substrate is still a challenging and urgent problem. In this article, the factors influencing the material distribution during the chemical vapor deposition process are investigated by a simulation method, and the results show that the unequal velocity distributions cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The final structure’s layer count, size, and orientation can be precisely tuned by manipulating various process parameters, including substrate type and orientation. A wide array of computational approaches, including finite element analysis, atomistic simulation, , and first-principles method, has been harnessed to provide insights into the synthesis of 2D material. While the majority of these investigations primarily center around first-principles/density functional theory (DFT) calculations, their scope remains limited in analyzing larger atomic systems found in TMDs exhibiting specific rotation angles. Consequently, it becomes imperative to employ alternative simulation techniques such as molecular dynamics (MD), , phase-field, , or multiscale models to gain a comprehensive understanding of the underlying mechanisms governing their growth.…”
Section: Introductionmentioning
confidence: 99%
“…The final structure’s layer count, size, and orientation can be precisely tuned by manipulating various process parameters, including substrate type and orientation. A wide array of computational approaches, including finite element analysis, atomistic simulation, , and first-principles method, has been harnessed to provide insights into the synthesis of 2D material. While the majority of these investigations primarily center around first-principles/density functional theory (DFT) calculations, their scope remains limited in analyzing larger atomic systems found in TMDs exhibiting specific rotation angles. Consequently, it becomes imperative to employ alternative simulation techniques such as molecular dynamics (MD), , phase-field, , or multiscale models to gain a comprehensive understanding of the underlying mechanisms governing their growth.…”
Section: Introductionmentioning
confidence: 99%
“…[23] For 2D TMDs, Zhou et al investigated the optimum boat geometry to grow a uniform MoSe 2 while Zhang et al reported velocity distribution of face-up or face-down substrate orientations. [24,25] However, analyses on surface deposition rate and precursors molar concentration were not discussed. Despite the potential of CFD in assisting the experiments, the simulation must be carried out with great care to ensure the accuracy of the predicted results.…”
Section: Introductionmentioning
confidence: 99%
“…Then the product of gaseous reactions deposits on the substrate, forming the 2D monolayer material. Various computational methods such as finite element analysis, atomistic simulation, , and the first-principle method have been employed to guide the synthesis of 2D materials. , Although most of these studies focus on first principal/DFT calculations, these simulations cannot analyze larger atomic systems involved in TMDs with certain rotation angles. Thus, in order to understand the mechanisms underlying their growth, other simulation techniques such as molecular dynamics (MD), phase-field, , or multiscale models need to be used.…”
Section: Introductionmentioning
confidence: 99%